Kinetics, isotherm and thermodynamics of sterol adsorption on styrene-divinylbenzene anion-exchange resins - Chinakrit Ladadok; Takehiro Yamaki; Keigo Matsuda; Hideyuki Matsumoto; Duangkamol Na-Ranong (My University, 2018)
Phytosterols can be recovered from natural resources using molecular distillation, cold crystallization, which require large energy consumption.Adsorption was considered as a feasible alternative method.In this study, kinetics, isotherm and thermodynamics of stigmasterol adsorption on styrene-divinylbenzene with two different functional groups, strong base (SB-R) and weak base (WB-R), were investigated using a model solution of stigmasterol in n-heptane.Isothermal adsorption experiments were performed in temperature range of 298-313 K and concentration range of 0.3-6.0mg/g sol .For both SB-R and WB-R cases, kinetics of adsorption was analysed based on pseudofirst-order and pseudo-second-order models and the results revealed that pseudo-second-order model agreed with the experimental data much better than pseudo-first-order model.Analysis of isotherm data based on Langmuir, Freundlich and linear models showed that Freundlich was the best model that could predict behaviour of sterol adsorption for both SB-R and WB-R cases.In addition, thermodynamics parameters (∆G, ∆H and ∆S) indicated that the sterol adsorptions on these adsorbents were spontaneous, exothermic and favourable at low temperature.
Keywords: Divinylbenzene; Ion-exchange resin; Sorption isotherm; Crystallization and Solubility Studies